Популяционный состав и динамика численности лесной мыши (Apodemus sylvaticus L.) (Mammalia, Muridae) в Алтагирском лесничестве Запорожской области - Филонов, К.П. (Вестник зоологии, 1978)
Regularities were studied in dynamics of a population quantity and composition. Interrelation is established between the dynamics of the population sex and weight composition and the quantity dynamics. The population composition influences the course of the quantity dynamics and the population density affects the population structure at a definite stage of fluctuation and homeostatic reactions are realized by means of changes in the reproduction potential.